Link Between Language And Character Development: People’s Perception - Oladunni O., Deji-Afuye; Tomi, Obadare Felicia (Advances in Social Sciences Research Journal, 2019)
This study addressed the importance of language for character and personality development. This was done in the perception of the respondents to the study. Two hundred (200) participants from Ikere Local Government Area of Ekiti States, Nigeria were randomly selected as the sample for this study. A self-developed questionnaire with Yes and No options was validated and administered to the respondents. The data collected were analyzed using chi-square analysis. The findings of the study showed that the use the language will significantly enhance character education, hence character development; and that the kind of language an individual is exposed to shapes the kind of character that is developed in such an individual. It is therefore recommended that the society should be well informed about the role language plays in the lives of its citizens; all stakeholders should be involved in character education program for every citizen; and that, character values should be integrated into all subjects in our schools.